2014
DOI: 10.4236/ojog.2014.43021
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum vascular endothelial growth factor correlated to three dimensional power Doppler indices in ovarian masses

Abstract: Objective: To assess the preoperative serum levels of vascular endothelial growth factor (VEGF) in ovarian masses compared to normal controls and to find a correlation between VEGF and Doppler indices in ovarian masses. Methods: The study was conducted from December 2009 to September 2012 in the oncology and ultrasound units in department of obstetrics and gynecology, Ain Shams University on 150 patients with ovarian masses. During preoperative workup, serum Ca-125 levels and serum VEGF levels were obtained. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…37 There is limited evidence with use of three dimensional and power Doppler indices for detection of malignancy. 21,38,39 Studies have demonstrated three dimensional power doppler indices to have a positive correlation with serum VEGF levels in ovarian masses. 21,38 Preoperative serum levels of vascular endothelial growth factor (VEGF) were correlated with three dimensional power Doppler indices in ovarian masses and the vascularization index (VI), flow index (FI) and vascularization flow index (VFI), correlated positively with serum VEGF levels, which were higher in malignant ovarian masses than in benign masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 There is limited evidence with use of three dimensional and power Doppler indices for detection of malignancy. 21,38,39 Studies have demonstrated three dimensional power doppler indices to have a positive correlation with serum VEGF levels in ovarian masses. 21,38 Preoperative serum levels of vascular endothelial growth factor (VEGF) were correlated with three dimensional power Doppler indices in ovarian masses and the vascularization index (VI), flow index (FI) and vascularization flow index (VFI), correlated positively with serum VEGF levels, which were higher in malignant ovarian masses than in benign masses.…”
Section: Discussionmentioning
confidence: 99%
“…21,38,39 Studies have demonstrated three dimensional power doppler indices to have a positive correlation with serum VEGF levels in ovarian masses. 21,38 Preoperative serum levels of vascular endothelial growth factor (VEGF) were correlated with three dimensional power Doppler indices in ovarian masses and the vascularization index (VI), flow index (FI) and vascularization flow index (VFI), correlated positively with serum VEGF levels, which were higher in malignant ovarian masses than in benign masses. 38 However, another study which evaluated the 3-D power Doppler indices concluded that VI, FI and VFI had a high intra-observer variability and low accuracy for identifying false positive results of IOTA simple rules.…”
Section: Discussionmentioning
confidence: 99%
“…41.36±16.33 years which are consistent with the previous study where mean age of benign cases was 37.0 ± 2.4 years and malignant cases 58.9 ± 6.3 years. 9 As with most cancers, the risk of developing ovarian cancer increases with older age. Similarly, in this study more than half of women with ovarian cancer belong to age e" 40 years.…”
Section: Methodsmentioning
confidence: 99%
“…Among malignant ovarian masses there were 63 epithelial carcinoma of ovary, Germ cell tumors were 7, sex cord stromal tumors were 2 and secondary ovarian tumor was 1. 9 Tahmina S. found that among the 96 adnexal masses 10(10.4%) cases were malignant, 33 cases were benign neoplastic, 1 was borderline and 52 cases were benign like tubo-ovarian masses, ectopic pregnancy, endometriotic cyst. 10 That study was done on nonneoplastic and neoplastic ovarian (benign and malignant) masses.…”
Section: Sample Size Determination and Sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation